Validity of the single limb heel raise test to predict lower extremity disablement in patients with sporadic inclusion body myositis. (December 2014) - Davenport, Todd E.; Shrader, Joseph A.; McElroy, Beverly; Rakocevic, Goran; Dalakas, Marinos; Harris-Love, Michael O.
Abstract Purpose: To determine the validity of the single limb heel raise (SLHR) test as a potential screening tool to detect lower extremity disability in patients with sporadic inclusion body myositis (sIBM). Methods: We compared gait speed and fall history between subjects with sIBM who either could complete one SLHR (SLHR group) or could not complete one SLHR. Discriminative validity was established by comparing between group differences in functional measures based on group assignment. Receiver operating characteristics curve analysis was used to determine the predictive validity of completing one repetition on the SLHR test. Spearman correlations were used to determine the association between gait kinematics and number of repetitions achieved on the SLHR test. Results: Forty-three subjects (13 females) were studied. The SLHR group (n = 21) showed significantly greater gait speed (p < 0.001) and decreased gait aid use (p < 0.05) compared to the no SLHR group (n = 22). SLHR cut scores of 1, 20, and 22 repetitions maximized positive likelihood ratios (+LR) for the ability to walk at 54.9 (+LR. 2.2), 63.2 (+LR. 9.5), and 73.1 m/min (+LR. 5.0), respectively. Conclusion: The SLHR test demonstrates adequate discriminative and predictive validity as a screening tool for lower extremity disablement in patients with sIBM. Implications for Rehabilitation The SLHR test has adequate reliability and validity to screen for the presence of lower extremity disablement in patients with sIBM. Results of this rapid field test may be used to guide the need for rehabilitation services to mitigate the effects of slow gait speeds in patients with sIBM.